THE INFLUENCE OF MEDIA AND LEARNING TECHNIQUES ON POETRY WRITING SKILLS IN SMPN IN BIMA DISTRICT - M. Syafii; Adi Apriadi Adiansha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2023)
Writing poetry requires not only good language skills, but also creative and imaginative skills. In today's digital era, the media and learning techniques used can influence the way students learn and understand poetry and help them develop better poetry writing skills. The research objectives were to find out 1) The effect of instructional media on the poetry writing skills of SMPN students in Bima district; 2) The influence of learning techniques on poetry writing skills of SMPN students in Bima district; 3) The effect of interactive media and learning techniques on the poetry writing skills of SMPN students in Bima district. The research method is an experiment with 2-way ANOVA analysis. The samples used were SMPN 1 Bolo and SMPN 1 Madapangga with a total of 120 students. Data collection using a written test. The results of the study show 1) There is a significant influence of learning media on students' poetry writing skills at Public Middle Schools in Bima Regency, West Nusa Tenggara Province. This is evidenced by the acquisition of Sig. = 0.000 <0.05 and Fh = 17.076; 2) There is a significant influence of learning techniques on students' poetry writing skills at Public Middle Schools in Bima District, West Nusa Tenggara Province. This is evidenced by the acquisition of Sig. = 0.000 <0.05 and Fh = 64.104; 3) There is a significant interaction effect of learning media and types of learning techniques on students' poetry writing skills at Public Middle Schools in Bima Regency, West Nusa Tenggara Province. This is evidenced by the acquisition of Sig. = 0.001 <0.05 and Fh = 11.273.